Effects Of Redundancy And Modality Principles In Video - Streaming On Attitude And Achievement - Abusaada, Ali H.M. (2013)
This study investigated the effects of modality and redundancy principles on the achievement and attitude among in-service teachers of different gender, computer skills and experience in Gaza. A "3x3" and "3x2" quasi experimental factorial design were adopted in this study. The independent variable was the three modes of video streaming on an ICDL course namely Video cum Narration (VN), Video cum Text (VT), Video cum Text and Narration (VTN). The moderator variables were the different gender, computer skills and experience of the in-service teachers. The dependent variables were the achievement (as measured by the post-test scores) and attitudes (as measured by attitudes questionnaire). The study sample consisted of 305 in-service teachers in the National Institute for Training in Gaza. ANCOVA was used to determine the significant differences in the post-test scores among the three treatment groups. Analyses of covariance (ANCOVA) were carried out to examine the main effects as well as the interaction effects of the independent variables on the dependent variables. The results showed that the teachers using the VN mode performed significantly better than learners using the VT mode and the VTN mode. There was no significant difference in post-test scores among male and female teachers. The VN mode was found to improve achievement and attitudes among learners with low computer skills, senior teachers and female teachers, as compared with the VT and VTN modes. In conclusion, the study supported the positive value and superiority of the VN mode. The modality and redundancy principles should be taken into consideration in the design and development of the video streaming lessons in order to improve learning.